2016
DOI: 10.1016/j.bcp.2015.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Proteasomal inhibition potentiates drugs targeting DNA topoisomerase II

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 59 publications
(87 reference statements)
8
33
0
Order By: Relevance
“…This was confirmed in human cells lacking TOP2B , where TOP2B null cells showed the greatest resistance to mAMSA and mitoxantrone, and also showed resistance to etoposide and doxorubicin. Notably, in this study TOP2B −/− null cells were significantly less sensitive to mAMSA and mitoxantrone than were TOP2A +/− heterozygotes, while for etoposide the TOP2A, heterozygotes demonstrated the greatest resistance [ 68 , 69 ]. Further evidence for targeting of TOP2B by TOP2 poisons was provided using a yeast ts top2 system expressing functional human TOP2B.…”
Section: Top2b As An Anti-cancer Drug Targetmentioning
confidence: 91%
“…This was confirmed in human cells lacking TOP2B , where TOP2B null cells showed the greatest resistance to mAMSA and mitoxantrone, and also showed resistance to etoposide and doxorubicin. Notably, in this study TOP2B −/− null cells were significantly less sensitive to mAMSA and mitoxantrone than were TOP2A +/− heterozygotes, while for etoposide the TOP2A, heterozygotes demonstrated the greatest resistance [ 68 , 69 ]. Further evidence for targeting of TOP2B by TOP2 poisons was provided using a yeast ts top2 system expressing functional human TOP2B.…”
Section: Top2b As An Anti-cancer Drug Targetmentioning
confidence: 91%
“…In this configuration, each protomer of the homodimeric TOP2 enzyme is covalently coupled to a cleaved DNA strand via a 5′-phosphotyrosine linkage. TOP2 poisons such as etoposide and mitoxantrone exert their tumoricidal effect by stabilizing this normally transient enzyme-bridged break, resulting in the accumulation of cytotoxic covalently linked TOP2 protein-DNA complexes, which can be processed in the cell to DNA double-strand breaks (Burma et al, 2001; Cowell and Austin, 2012; Lee et al, 2012, 2016). Therapy related leukemias, especially those appearing after exposure to TOP2 poisons often contain recurrent chromosome translocations, including t(15,17)(PML-RARA) , t(8,21)(AML-ETO) , and 11q23 rearrangements involving the MLL gene (Rowley and Olney, 2002; Cowell and Austin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, specifically blocking the degradation of TOP2β would be a better choice for effectively enhancing the anticancer efficacy of TOP2 poisons. However, the proteasomal inhibitors used in a previous study are associated with high normal cell toxicity, as a result of the global inhibition of protein degradation through the 26 S proteasome 35 . In this study, we revealed the precise mechanism by which TOP2 poisons induce TOP2β degradation and demonstrated that specifically blocking TOP2β degradation remarkably sensitizes cancer cells to VM-26 treatment (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study showed that proteasomal inhibitors significantly enhance the growth inhibition of drugs targeting DNA topoisomerase II, indicating that blocking TOP2 degradation is an attractive strategy to sensitize cancer cells to TOP2-targeting chemotherapeutic drugs (TOP2 poisons) 35 . Although TOP2 poisons induce the degradation of both TOP2α and TOP2β, the rate and extent of degradation are much greater for TOP2β than for TOP2α ( Fig.…”
Section: Discussionmentioning
confidence: 99%